Viana, a Sé - Marta Oliveira (2005)
Viana, the See The old square and the parish church have a common layout that determines, as in an interface, the pattern of the urban space and its built-up scale. The church's shape is inspired by Romanesque architecture. its spans having a regular rhythm, with emphasis on the area just before the chancel that will be turned into a transept. The building itself fits in with contemporary port village churches, while the amplitude of arcades and volume within the church attest to an innovating space concept, much in line with the time of construction. From the beginning, the parish church embodied an aspiration to be raised to the rank of episcopacy, considering Viana's ancient tradition of Christian occupation. The church Romanesque-Bizantine frontispiece was reviewed in the light of the 19th century scientific spirit, through the reinforcement of a 14th century battle reminiscence that extended to the church interior.